Teaching school jazz perspectives, principles, and strategies - West, Chad ca. 20./21. Jh; Titlebaum, Michael 1968- (Oxford University Press, 2019)
'Teaching School Jazz' is an edited collection of suggested practices in school jazz education authored by a seasoned and diverse lineup of jazz educators with supporting research-based case studies woven into the narrative. It provides not only a wealth of school jazz teaching strategies but also, and perhaps as important, the jazz perspectives and principles from which they are derived
Also issued in print: 2019. - Includes bibliographical references and index
Keywords: Jazz / Instruction and study; Musikerziehung; Schule; Jazz; USA; Aufsatzsammlung